M. Quraish Shihab, Menggugat Bias Gender “Para Ulama” - Naqiyah Mukhtar (JOURNAL OF QUR'AN AND HADITH STUDIES, 2013)
Some of the ulama’s views related to women (the origin of creation, temptressness and lack of rationality), are considered to be biased and misogynistic by M. Quraish Shihab. These viewpoints, according to Shihab, rooted in long-standing old views that harrassed and marginalized women. These views cannot be justified either by reasons or religion, although some of them used religious texts. This article addresses Shihab’s criticism against the views of scholars that he considers to be biased. The data are obtained from the works of M. Quraish Shihab, particularly on Perempuan in addition to al-Misbah. The data are analyzed using content analysis and gender perspectives. The significance of this study is to show that the religious texts (both the Qur’an and Hadith) associated with women tend to be interpreted in accordance with mufassir’s perception.